Is outsourcing healthcare to private providers associated with higher mortality rates in NHS England?. (20th October 2021) - Goodair, B; Reeves, A; Rahal, C
Abstract: Background: Outsourcing services to for-profit organisations within a publicly funded healthcare service which runs parallel to private provision in a 'two-tier' system aims to increase the competition between healthcare providers, driving up their performance. However, some worry that contracting out health services to for-profit providers may lead to cost-cutting and poorer outcomes for patients. We aim to assess whether increased outsourcing to the private sector is associated with changes to treatable mortality rates, and, therefore, with the quality of healthcare. Methods: We construct a novel database compiling every procurement contract over 7 years (n = 646, 938, total value = £204.1bn) across England's Clinical Commissioning Groups (regional health boards). We identify institutions registered on the Companies House registry which supply regional commissioners in England's NHS, and then aggregate this annually with local mortality data. By exploiting the commissioners' variation in spend on private sector providers, we estimate the association between outsourcing and treatable mortality rates in the following year. We account for year and individual fixed effects and control for multiple covariates, including average household income, Local Authority spending, and population size. Results: Our sample comprised 173 Clinical Commissioning Groups between 2013 and 2020. In general, outsourcing increased over this period, but the extent of change varied substantially. Some areas, like East Riding of Yorkshire, saw very large increases but others saw reductions. We find an annual increase of one percentage point of outsourcing to the private sector corresponds with an annual increase in treatable mortality of 0.34% (95% CI 0·10% to 0·58%) in the following year. Conclusions: The incorporation of private sector providers into England's NHS appears to be corresponding with a decline in the quality of healthcare services. Key messages: The private provision of healthcare services has generally increased across England's NHS since 2013. Increased outsourcing of services to private sector providers is associated with increased treatable mortality rates.